PERANCANGAN SISTEM INFORMASI MANAJEMEN PERUSAHAAN “GEN-Z” MENGGUNAKAN METODE AGILE BERBASIS WEBSITE - Ega Bagus Purnama; Germecca Germecca; Niza Aidha Wardhani; Nurul Azizah (Hemispheres Press, 2023)
The development of information technology has had a significant impact on modern companies, affecting the way companies manage information and carry out their operations. In the digital era dominated by generation Z, it is important for companies to adopt an effective and efficient management information system to support their business activities.The purpose of this research is to design a website-based management information system for